PENDIDIKAN KEPERAWATAN: UPAYA MENGHASILKAN TENAGA PERAWAT BERKUALITAS - Lestari, Tri Rini Puji (Jurnal Aspirasi, 2014)
Arrangements regarding the establishment and organization of nursing education are still not decisive and visible. As a result, general recognition of nursing as a profession and the number of nurses that dominates the health workforce have not been optimal. This paper uses descriptive qualitative analysis method as an approach to the study of literature. The purpose of this study is to determine the current condition of and the future hope for nursing education system, as to create quality nurses. Based on the results of the study, in order to create quality nurses there is a need for quality nursing education. It is because nursing education is an important process that every nurse must undertake. This is an effort for quality assurance of nursing education which required necessary standards of research and development of nursing education.